2020
DOI: 10.3389/fcell.2020.00744
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Xist Contributes to Endogenous Neurological Repair After Chronic Compressive Spinal Cord Injury by Promoting Angiogenesis Through the miR-32-5p/Notch-1 Axis

Abstract: Endogenous repair after chronic compressive spinal cord injury (CCSCI) is of great clinical interest. Ischemia-hypoxia-induced angiogenesis has been proposed to play an important role during this repair process. Emerging evidence indicates that long non-coding RNAs (lncRNAs) are involved in the pathophysiological processes of various diseases. Here, we identified a lncRNA (Xist; X-inactive specific transcript) with upregulated expression in cervical spine lesions during endogenous neurological repair in CCSCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
(61 reference statements)
2
34
0
Order By: Relevance
“…DAPT solution (1 μg/μL) was prepared by dissolving DAPT powder (MCE, United States) in 0.01 M phosphate-buffered saline (PBS) containing 5% dimethyl sulfoxide. The DAPT solution (1 mg/kg per rat) and a negative control were intraperitoneally injected using a microinjection syringe ( Cheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…DAPT solution (1 μg/μL) was prepared by dissolving DAPT powder (MCE, United States) in 0.01 M phosphate-buffered saline (PBS) containing 5% dimethyl sulfoxide. The DAPT solution (1 mg/kg per rat) and a negative control were intraperitoneally injected using a microinjection syringe ( Cheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…[18] Our previous study showed that 4 weeks of chronic compression led to a severe ischaemia-hypoxia environment, as demonstrated by increased HIF-1α expression, [25] and signi cantly decreased microvascular density, as demonstrated by micro-CT and immunohistochemistry data. [39,49] Thus, the increased T2WI hyperintensity in our study was more likely to represent transient ischaemia upon exion. We assume that the CCSCI models, whose spinal cord circulation was already compromised, suffered more perfusion decrease upon exion than sham mice.…”
Section: Discussionmentioning
confidence: 67%
“…In LPS-induced SCI (Spinal cord injury) microglia cells and lncRNA Xist, which interacts with miR-27a to mediate the downstream target gene of Smurf1 expression, alleviated the apoptosis and inflammatory injury of microglia cells after SCI through activating miR-27a/Smurf1 axis ( Zhao Q. et al, 2020 ). These signaling pathways, which include lncRNA Xist/miR-494/PTEN/PI3K/AKT signaling pathway ( Gu et al, 2017 ), lncRNA Xist/miR-142-5p/PDCD4 signaling pathway ( Tang et al, 2020 ), lncRNA Xist/miR-217/TLR4 signaling pathway ( Jin et al, 2019 ), lncRNA Xist/miR-32-5p/Notch-1 signaling pathway ( Cheng X. et al, 2020 ), and lncRNA Xist/miR-15a-5p/CUL3signaling pathway ( Xu et al, 2019 ), participated in the SCI, acute kidney injury, and nephropathy procession. Cheng and Wang (2020) identified that lncRNA Xist could act as a ceRNA to sponge miR-212-3p and miR-122-5p to facilitate kidney transplant acute kidney injury progression via regulating the expression of ASF1A, BRWD1, and PFKFB2 using GEO database assay.…”
Section: The Role Of Lncrna Xist In Non-cancer Diseasesmentioning
confidence: 99%